2022
DOI: 10.1210/clinem/dgac445
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Resistance Training Is Associated With Better HR-pQCT–derived Bone Microarchitecture in Vegan People

Abstract: Context Plant-based lifestyle is a global trend, lower bone mineral density and increased fracture risk in vegan people are reported. Objective Primary objective: To assess trabecular and cortical bone microarchitecture in vegans and omnivores. Secondary objectives: To evaluate relationships between bone microarchitecture, nutrition parameters and physical activity. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…These deficiencies can manifest as fatigue and poor injury healing, which would all drastically impact athletic performance, recovery, and overall bone health. A recent study showed that vegan athletes had poorer bone quality compared to omnivores and had decreased benefit in bone quality from resistance training than omnivores as well [ 78 ]. While this study has not been further studied in additional athlete specific populations, this reflects a similar trend in a systematic review studying the general female population [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…These deficiencies can manifest as fatigue and poor injury healing, which would all drastically impact athletic performance, recovery, and overall bone health. A recent study showed that vegan athletes had poorer bone quality compared to omnivores and had decreased benefit in bone quality from resistance training than omnivores as well [ 78 ]. While this study has not been further studied in additional athlete specific populations, this reflects a similar trend in a systematic review studying the general female population [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with omnivores, peripheral skeleton trabecular and cortical microstructure were altered in vegan people [ 16 ]. The differences were attenuated in the subgroup reporting regular resistance training.…”
Section: Dietary Patternsmentioning
confidence: 99%
“…Into the argument has entered a group from Vienna (Austria), who used high-resolution CT to examine bone microarchitecture and correlated this with dietary choices. 6…”
Section: Self-reported Resistance Training Is Associated With Better ...mentioning
confidence: 99%
“…Into the argument has entered a group from Vienna (Austria) , who used high-resolution CT to examine bone microarchitecture and correlated this with dietary choices. 6 Studying 43 vegans and 45 omnivores, the team found that vegans who did not carry out resistance training showed reduced trabecular and cortical density when compared to non-training omnivores, although this relationship was not present in cohorts who conducted resistance training. No other meaningful correlations were identified.…”
Section: Self-reported Resistance Training Is Associated With Better ...mentioning
confidence: 99%